2020
DOI: 10.1038/s41598-020-64344-2
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes impacts colorectal adenoma detection in screening colonoscopy

Abstract: Background: Diabetes is associated with an increased risk of colorectal cancer (CRC). We conducted a retrospective analysis of adenoma detection rates (ADR) in initial screening colonoscopies to further investigate the role of diabetes in adenoma detection. Methods: A chart review was performed on initial average risk screening colonoscopies (ages 45–75) during 2012–2015. Data collected included basic demographics, insurance, BMI, family history of CRC, smoking, diabetes, and aspirin use. Multivariable general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Epidemiological statistics and meta-analysis results showed that patients with T2DM had a higher risk of CRC ( 53 ). Accordingly, timely administration of drugs to control blood glucose in these patients was helpful in reducing the incidence of colorectal adenoma ( 54 ). A recent report from Sweden’s large-scale epidemiological statistics, including 12,614,256 individuals (comprising 559,375 patients with diabetes and 162,226 patients with CRC), followed up between 1964−2015 showed that a personal diabetes history increases the risk of CRC (0.4%) comparably with a family history of CRC (0.5%) in patients diagnosed with diabetes at <50 years old ( 55 ).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Epidemiological statistics and meta-analysis results showed that patients with T2DM had a higher risk of CRC ( 53 ). Accordingly, timely administration of drugs to control blood glucose in these patients was helpful in reducing the incidence of colorectal adenoma ( 54 ). A recent report from Sweden’s large-scale epidemiological statistics, including 12,614,256 individuals (comprising 559,375 patients with diabetes and 162,226 patients with CRC), followed up between 1964−2015 showed that a personal diabetes history increases the risk of CRC (0.4%) comparably with a family history of CRC (0.5%) in patients diagnosed with diabetes at <50 years old ( 55 ).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Patients who underwent index screening colonoscopies at Kings County Hospital from January 1, 2017, until December 31, 2018, were identified using endoscopy reporting software. Patients aged < 45 years or > 75 years or with a history of previous colonoscopy, a history of inflammatory bowel diseases, known hereditary colorectal syndromes, detection of microscopic or macroscopic blood in stool and other alarm syndromes, or detection of colonic masses or polyps in previous studies were excluded from this analysis as previously described[ 14 , 15 ]. Colonoscopies that were incomplete (did not reach the cecum) and those associated with poor bowel preparation were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Colonoscopies that were incomplete (did not reach the cecum) and those associated with poor bowel preparation were also excluded. Clinical metadata were manually collected on each patient using electronic medical records (EMRs) as documented at the time of screening colonoscopy and included (1) age at time of initial screening colonoscopy (year); (2) sex (Male, Female); (3) race (White/EA, Black/AA, Asian, Other); (4) Hispanic ethnicity; (5) Insurance (Commercial, Medicare, Medicaid, Self-pay); (6) BMI (kg/m 2 ); and (7) Tobacco Exposure (Current within one year, Past greater than one year, Never)[ 14 , 15 ]. A family history of a first-degree relative of CRC was not included in the analysis because of incomplete documentation in the EMR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations